Natural Products as A Promising Therapy for SARS COV-2; An Overview - Jaafar, Noor S.; Jaafar, Iman S. (Iraqi Journal of Pharmaceutical Sciences, 2021)
Recently emerging pandemic SARS CoV-2 conquered our world since December 2019. Continuous efforts have been done to find out effective immunization and precise treatment stetratigies A way from therapeutic options that were tried in SARS CoV-2, an increased attention is directed to predict natural products and mainly phytochemicals as collaborative measures for this crisis. In this review, most of the mentioned compounds specially flavonoids (biacalin, hesperidin, quercetin, luteolin,, and phenolic (resveratrol, curcumin, and theaflavin) exert their effect through interfering with the action of one or more of this proteins (spike protein, papain like protease, 3 chymotrypsin like cysteine protease, and RNA dependent RNA polymerase) that are involved in viral life cycle beside the anti-inflammatory effect of these compounds. The triterpenoids (celastrol, escin and glycyrrhizin) and the alkaloids (lycorine and cepharanthine) mediated their effect mainly through anti-inflammatory activity. Glycyrrhetinic acid (glycyrrhizin metabolite) dawn regulates ACE 2, and reduces protease expression, thus reduce viral entry. This review may be representing an initial step in long path for designing the successful and effective treatment or vaccine for this pandemic.